1991
DOI: 10.1002/mrd.1080280307
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous cell contacts and metabolic coupling in bovine cumulus oocyte complexes

Abstract: The integrity of the cumulus cell processes were studied in four categories of bovine cumulus oocyte complexes (COCs) selected on their morphological characteristics. Three different types of cumulus cell process endings (CCPEs) were identified, one penetrating the cortex, another not penetrating the cortex, and a third form was intermediate and more rare in appearance. The process endings that penetrated the cortex frequently made gap junctions with the oolemma. The division of the three types of CCPEs over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
7

Year Published

1994
1994
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 16 publications
2
37
0
7
Order By: Relevance
“…These data support the idea that maintaining the cumulus-oocyte connection is essential for oocyte cytoplasmic maturation. Furthermore, the relative smaller oocyte diameter in the 0L-COC group (;99.7 lm) indicated that these oocytes might originate from less developed follicles [40,41], and the lack of surrounding cumulus suggested that they might be from earlier atretic follicles [42]. Compared to the ML-COC group, there were fewer oocytes in the 1L-COC group that progressed to MII.…”
Section: Discussionmentioning
confidence: 88%
“…These data support the idea that maintaining the cumulus-oocyte connection is essential for oocyte cytoplasmic maturation. Furthermore, the relative smaller oocyte diameter in the 0L-COC group (;99.7 lm) indicated that these oocytes might originate from less developed follicles [40,41], and the lack of surrounding cumulus suggested that they might be from earlier atretic follicles [42]. Compared to the ML-COC group, there were fewer oocytes in the 1L-COC group that progressed to MII.…”
Section: Discussionmentioning
confidence: 88%
“…Intercellular communications within the ovarian follicle have been implicated in the control of meiotic arrest and maturation of mammalian oocytes, and such a metabolic coupling in cumulus-oocyte complexes (COCs) before the beginning of maturation has been demonstrated to be essential in the acquisition of developmental competence [10].…”
Section: Introductionmentioning
confidence: 99%
“…Este sucesso limitado pode ser parcialmente atribuído aos métodos de seleção dos COCs, baseados exclusivamente em parâmetros morfológicos avaliados ao estereomicroscópio, tais como a morfologia do ooplasma e do cumulus, o tamanho do folículo e do ovócito, e o grau de atresia folicular. Os COCs com massa de cumulus compacta e constituída por numerosas camadas de células foliculares, e com um ovócito de ooplasma homogêneo, apresentam maior capacidade de desenvolvimento, contrastando com os COCs de cumulus expandido e ooplasma heterogêneo (De Loos et al, 1989, 1991.…”
Section: Introductionunclassified